PENDAFTARAN MEREK SEBAGAI BENTUK PERLINDUNGAN HUKUM PADA USAHA MIKRO KECIL DAN MENENGAH DI KOTA PALU - ain, Ain Safitri (Jurnal Ilmu Hukum Lasadindi, 2024)
The research method used is Empirical research, by examining or analysing in the form of primary data and secondary data. The results showed that the cause of MSME actors in Palu City, especially South Palu and West Palu, did not register their trademarks due to lack of knowledge of intellectual property rights, especially trademarks and lack of legal understanding, limited costs, and lack of counseling and socialisation. The Department of Industry and Trade of Palu City has played an important role in encouraging trademark registration for MSMEs in Palu City by providing information, collaborating with relevant agencies, facilitating the registration process, providing guidance and consultation. Although the efforts made by the Office of Industry and Trade of Palu City have not been evenly distributed, the efforts show the commitment of the Office of Industry and Trade of Palu City in encouraging trademark registration for MSMEs in Palu City.